(untitled) (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of transformational leadership on employee engagement at PT X Sidoarjo. The research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 183 respondents, who are employees of PT X Sidoarjo. Data analysis was conducted using simple linear regression to examine the relationship between the independent and dependent variables. The results indicate that transformational leadership has a positive effect on employee engagement, with a correlation value of r = 0.370 and a contribution of 29.5%, while the remaining 70.5% is influenced by other variables not examined in this study. The conclusion of this study is that the higher the implementation of transformational leadership, the higher the level of employee engagement. Therefore, companies are advised to enhance transformational leadership competencies through training and development to improve employee engagement within the organization.